Effectiveness of a mindfulness program on psychological distress among preclinical medical students in a public university in Malaysia - Fuad, Maher D Fuad (2018)
Background: Psychological distress (PD) is common among medical students. Many studies used mindfulness based interventions (MBI) to reduce psychological distress and enhance coping mechanisms. However, the duration of the commitment required to attend these interventions led to many prospective participants to either withdraw or not participating in the programs. Many studies explored shorter versions of MBI and found it successful in reducing psychological distress. Objectives: To determine the prevalence and risk factors of PD, depression, anxiety and stress (DAS) among preclinical medical students. Also, this study aimed to determine the effectiveness of The Mindfulness Program (TMP) on PD and DAS among preclinical medical students. Methodology: This study had two phases. Phase 1 was a cross sectional study. Phase 2 was an experimental study. A total of 237 preclinical undergraduate medical students were screened in phase 1 of the study. 92 students with high scores of PD were recruited for phase 2 of the study. Subjects were randomly allocated to TMP and wait-listed control groups on a one to one ratio. Only one trainer implemented the intervention. Self-administered validated questionnaires were used to record data for the study. Participants filled the baseline questionnaires two weeks prior to end of semester exam. The post intervention questionnaires were filled 8 weeks after the intervention and two weeks prior to the end of semester exam. Primary and secondary outcomes of the study were PD and DAS. Results: The prevalence of PD was 38.8%. The prevalence of stress, anxiety and depression were 37.1%, 51.9% and 24.1% respectively. Risk factors of PD included academic related stressors (Adjusted Odds Ratio (AOR)= 1.65, 95% C.I. = 1.01, 2.71, p= 0.047), drive and desire related stressors (DRS) (AOR=1.44, 95% C.I. = 1.02, 2.03, p=0.039) and group-activities related stressors (GARS) (AOR= 1.74, 95% C.I. = 1.12, 2.69, p= 0.014). Risk factors of depression included male preclinical medical students (AOR= 5.71, 95% C.I.=2.64, 12.36, p<0.001), living in rural areas (AOR= 3.38, 95% C.I. =1.48, 7.72, p=0.004), DRS (AOR= 1.51, 95% C.I. = 1.03, 2.20, p=0.035), GARS (AOR= 3.58, 95% C.I.=2.24, 5.72, p<0.001). Risk factors of anxiety included living in rural areas (AOR= 2.40, 95% C.I. =1.26, 4.59, p value = 0.008) and GARS (AOR= 2.56, 95% C.I. =1.80, 3.64, p<0.001). Risk factors of stress included living in rural areas (AOR= 2.41, 95% C.I.=1.07, 4.27, p=0.031), GARS (AOR= 2.60, 95% C.I.=1.72, 3.95, p<0.001) and teaching and learning related stressors (AOR= 1.79, 95% C.I. =1.16, 2.78, p=0.009). Intention to treat analyses using repeated measures analyses of covariance showed significant mean scores reduction of PD (p=0.002), stress (p<0.001), anxiety (p<0.001), and depression (p=0.001) among TMP group. Conclusions: Preclinical medical students had a high prevalence of PD and DAS. Important risk factors were identified. TMP showed a significant reduction in mean scores of PD and DAS in the intervention group compared to the control wait-listed group.